2009
DOI: 10.1038/sj.bjc.6605258
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative downstaging chemoradiation with concurrent irinotecan and capecitabine in MRI-defined locally advanced rectal cancer: a phase I trial (NWCOG-2)

Abstract: Background:The aim of this study was to investigate the safety of neoadjuvant chemoradiation using radiotherapy (RT) combined with concurrent capecitabine and irinotecan for locally advanced rectal cancer before surgery.Methods:Forty-six patients were recruited and treated on the basis that MRI scanning had shown poor-risk tumours with threatening (⩽1 mm) or involvement of the mesorectal fascia. Conformal RT was given using 3 or 4 fields at daily fractions of 1.8 Gy on 5 days per week to a total dose of 45 Gy.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 27 publications
1
16
0
Order By: Relevance
“…The study has demonstrated the successful application of multicomponent treatment including four radiosensitizers. Despite the large number of treatment components, grade III−IV toxicity was comparable with the 21−43% reported in trials with comparable chemoradiotherapy regimes .…”
Section: Discussionsupporting
confidence: 61%
“…The study has demonstrated the successful application of multicomponent treatment including four radiosensitizers. Despite the large number of treatment components, grade III−IV toxicity was comparable with the 21−43% reported in trials with comparable chemoradiotherapy regimes .…”
Section: Discussionsupporting
confidence: 61%
“…Gollins et al [42] used MRI scanning to identify high-risk rectal cancer patients, defined as involvement or threatening involvement (1 mm or less) of the mesorectal fascia. Neoadjuvant radiation therapy up to 45 Gy with concurrent escalating doses of both daily capecitabine and weekly inrinotecan was given from day 1-35.…”
Section: Clinical Data Neoadjuvant Trialsmentioning
confidence: 99%
“…On the other hand, Gollins et al [14], Aschele et al [22], Sato et al [23] as well as Voelter et al [8] report rather low anastomotic leakage rates of 6.4%, 2%, 0% and 6% respectively from a group of 31, 747, 67 and 21 patients with sphincter sparing surgery. All studies concerning an intensified neoadjuvant RCT regime lack either a substantial number of patients and are basically series without a control group or do not focus on the surgical outcome [5,15,22,23].…”
Section: Discussionmentioning
confidence: 99%